Experimental Study of Confined Low-, Medium- and High-Strength Concrete Subjected to Concentric Compression - Antonius, Antonius; Imran, Iswandi (Journal of Engineering and Technological Sciences, 2012)
An  experimental  study  of  23  low-,  medium-  and  high-strengthconcrete  columns is presented in this paper. Square-confined concrete columns without  longitudinal  reinforcement  were  designed,  and  tested  under  concentric axial  compression.  The  columns  were  made  of  concrete  with  a  compressive strength ranging between 30 MPa and 70 MPa. The test parameters in the study are  concrete  compressive  strengths  and  confining  steel  properties,  i.e.  spacing, volumetric  ratios  and  configurations.  The  effects  of  these  parameters  on  the strength  and  ductility  of  square-confined  concrete  were  evaluated.  Of  the specimens tested in this study, the columns made with higher-strength concrete produced less strength  enhancement and ductility than those with lower-strength concrete.  The  steel  configurations  were  found  to  have  an  important  role  in governing  the  strength  and  ductility  of  the  confined  high-strength  concrete. Moreover,  several  models  of  strength  enhancement  for  confined  concrete available  in  the  literature  turned  out  to  be  quite  accurate  in  predicting  the experimental results.